Dalla monarchia a una repubblica senza democrazia. Tocqueville e i nodi dell’indipendenza messicana - Maremonti, Ludovico (Studi Politici, 2023)
In Democracy in America, Alexis de Tocqueville criticized the Hispanic-American republics and especially the Mexican federal republic founded in 1824, for being unsuccessful imitations of the original Anglo-American model. However, Tocqueville does not seem delving into how Mexico became a federal republic, after an ephemeral experience as a constitutional Empire leaded by the Liberator Agustín de Iturbide at the beginning of her independent history. This work aims to point out some peculiarities of the process of Mexico becoming a federal republic, also trying to interpret under Tocqueville’s political categories the failure of the monarchy that caused the emergence of the 1824 Federation.